A Review on Phytochemical and Pharmacological Aspects of Ochradenus baccatus - Lohit Kumar Dadi; Raman Patyar Rakesh; Aidaroos Thabit Ahmed Alsaadi Mohamed; Patyar Sazal (BIO Web of Conferences, 2024)
Ochradenus baccatus, also known as "Taily Weed," is a perennial shrub that belongs to the Resedaceae family and is often used as a folk medicine for the treatment of headache, fever or sexual disorders in the Middle Eastern countries. It is also used as an antibiotic, cooling agent and deodorant. Due to its widespread use in traditional medicine in the Middle Eastern countries and lack of scientific evidence, it is being investigated for its phytotherapeutic potential in different disease conditions.